Temporal distribution of Botrytis cinerea and its relationship to the production of strawberries (Fragaria × ananassa Duch., Monterrey variety) subjected to biological treatments with microbial antagonists (2023)
In the Bogota Plateau (Bogota Savanna-Colombia), strawberry cultivation (Fragaria × ananassa Duch.) is established from 2,000 to 2,800 m a.s.l. In this environment the relative humidity is generally greater than 70% and the temperature fluctuates between 14 and 22°C; this is a favorable climate for the development of fungal diseases. Gray mold (Botrytis cinerea) is the most important disease here and fruit losses can exceed 40% of production. The purpose of this research was to analyze the effect of the use of microbial antagonists in the biological regulation of B. cinerea and its relationship to production. Fragaria × ananassa Duch, cv. Monterrey plants were inoculated and co-inoculated (combination) at the time of transplantation with microbial consortia made up of mycorrhizal fungi, antagonistic bacteria and Trichoderma harzianum. We evaluated the temporal incidence of B. cinerea and the production of healthy fruits at 90, 180 and 270 days after transplantation. We observed a temporary increase in the incidence of the disease from 6.59 to 23.08% in the control plants, and higher values than those observed with biological treatment. Treatment with mycorrhizae showed the lowest values of B. cinerea with values from 0.89, 13.78% and the best treatment in fruit production. Inoculation and co-inoculation are an alternative for reducing the incidence of disease and for increasing fruit production.